Effect of Occurrence of Lamin A/C (LMNA) Genetic Variants in a Cohort of 101 Consecutive Apparent “Lone AF” Patients: Results and Insights - Pessente, Gabrielle D'Arezzo; Sacilotto, Luciana; Calil, Zaine Oliveira; Olivetti, Natalia Quintella Sangiorgi; Wulkan, Fanny; Oliveira, Théo Gremen Mimary de; Pedrosa, Anísio Alexandre Andrade; Wu, Tan Chen; Hachul, Denise Tessariol; Scanavacca, Maurício Ibrahim; Krieger, José Eduardo; Darrieux, Francisco Carlos da Costa; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Mutations in the LMNA gene are commonly associated with cardiac manifestations such as dilated cardiomyopathy and conduction system disease. However, the overall spectrum and penetrance of rare LMNA variants is unknown. The present study describes the presence of LMNA variants in patients with “lone atrial fibrillation (AF)” as their sole clinical presentation. Methods: One-hundred and one consecutive patients with “lone AF” criteria were initially screened by genetic testing. Genetic variants were classified according to the American College of Genetic and Genomic criteria. All subjects were evaluated through clinical and familial history, electrocardiogram, 24-hour Holter monitoring, echocardiogram, cardiac magnetic resonance, and treatment response, as well as the presence relatives of LMNA-carriers. In addition, whole-exome data from 49,960 UK Biobank (UKB) participants were analyzed to describe the overall penetrance of rare LMNA missense and loss of function (LOF) variants. Results: Three missense variants in LMNA were identified in probands with AF as their first and unique clinical manifestation. Other five first degree relative, after screening, also presented LMNA gene variants. Among 49,960 analyzed UKB participants, 331 carried rare LMNA missense or LOF variant. Participants carrying a rare LMNA variant were significantly associated with higher odds of arrhythmic events and of an abnormal electrocardiogram (ECG) in the per protocol ECG exam (p=0.03 and p=0.05, respectively). Conclusion: Although a rare occurrence, our findings emphasize the possibility of an initial presentation of apparently “lone AF” in LMNA gene variant carriers.